The Pegon Script and Integrated Islamic Education in Yogyakarta: Study of the Alala Book Subject in Al-Qodir Islamic Boarding School - Pairin Pairin (STAI Hubbulwathan Duri, 2023)
The Alala book, which contains simple and essential content for the students and its translation in the Javanese Pegon script, is the main factor why the Alala book was chosen. Talking about the narrative of the Alala book—assuming that it can be expanded to a broader and systematic scope—this research tries to look back to what extent the Alala book intersects with the ideas of integrated education. The authors also observe at the level of teaching-learning practice, namely how the portrait appears when studying the Alala book at Al-Qodir Islamic boarding school with an integrated lens concerning the Alala's natural form. The integrated framework includes simultaneous models, attention to the cultural identity domain, and the connection between knowledge and experience. The results show that the Alala book's nature supports ideas of simultaneity, culture-identity, participation with direct experience, and heart involvement. It can demonstrate an integrated learning model in the educational program of Islamic boarding schools when the students study it properly.